A Rapid Method for the Determination of Buprenorphine and Norbuprenorphine in Urine by UPLC-MS/MS - Kul, Aykut; Ozdemir, Murat; Ozilhan, Selma; Sagirli, Olcay (Current Pharmaceutical Analysis, 2021)
Background: Buprenorphine is quite common in the illicit market. Buprenorphinecontaining drug abuse is frequently encountered in patients. The analysis methods used to determine the abuse of buprenorphine and norbuprenorphine are important for forensic science. Buprenorphine is metabolized to norbuprenorphine by the liver. Objective: Therefore, the determination of buprenorphine and norbuprenorphine in urine is one of the methods to determine the abuse of buprenorphine. Methods: In this study, we developed a precise, simple, and rapid ultra-performance liquid chromatography- tandem mass spectrometer method for the determination of buprenorphine and norbuprenorphine simultaneously. Results: The developed method was validated in terms of selectivity and linearity, which was in the range of 9–1800 ng/mL for both buprenorphine and norbuprenorphine. The intra-assay and inter-assay accuracy and precision were found within acceptable limits of the EMA guideline. Lower limits of quantitation were 9 ng/mL for both buprenorphine and norbuprenorphine. Conclusion: The developed method was successfully applied for the determination of both analytes in the proficiency testing samples.
Keywords: Buprenorphine